Complaint Offense Application Effectiveness against the Creator’s understanding of Copyright Infringement - Adhitama, Miftahul Rizky (ADLIYA: Jurnal Hukum dan Kemanusiaan, 2022)
With a broad scope of Copyright in Indonesia, its regulation must develop progressively following human behavior development, including overcoming the offense against it. This writing presents the effectiveness of applying complaint offense and factors that affect its effectiveness. This research uses the empirical juridical approach. This study found that the complaint offense does not necessarily prohibit law enforcement officials from initiating investigations without any complaint, at least until the case is filed. A synergy between the state and individuals (creators) will suppress the number of copyright infringements in Indonesia. Based on the widespread practice of piracy in society, the factor inhibiting the effectiveness of law enforcement lies in the lack of understanding of the concept of copyright protection. Law enforcement can only take action against copyright offenders by confirming the embodiment between the expression of the complainant’s copyrighted work and the alleged one. Copyright Law enforcement still needs the presence of practical means and adequate infrastructure to minimize basic reporting errors due to misÂrecogÂnizing the characteristics of copyright infringement. Dengan cakupan Hak Cipta yang luas di Indonesia, pengaturan tentangnya harus berkembang secara progresif mengikuti perkembangan perilaku manusia, termasuk mengatasi pelanggaran terhadapnya. Tulisan ini memaparkan efektivitas penerapan delik aduan dan faktor-faktor yang mempengaruhi efektivitasnya. Penelitian ini menggunakan pendekatan yuridis empiris. Studi ini menemukan bahwa delik aduan tidak serta merta melarang aparat penegak hukum memulai penyelidikan tanpa adanya pengaduan, setidaknya sampai gelar perkara dilakukan. Sinergi antara negara dan individu (pencipta) akan menekan angka pelanggaran hak cipta di Indonesia. BerdasarÂkan maraknya praktik pembajakan di masyarakat, faktor penghambat efektifitas penegakan hukum terletak pada kurangnya pemahaman tentang konsep perlindungan hak cipta. Penegak hukum hanya dapat menindak pelanggar hak cipta dengan menegaskan perwujudan antara ekspresi karya berhak cipta pelapor dan yang diduga. Penegakan hukum Hak Cipta masih membutuhkan adanya sarana praktis dan infrastruktur yang memadai untuk meminimalkan kesalahan pelaporan dasar karena salah mengenali karakteristik pelanggaran hak cipta.